Analisis Digital Watermarking untuk Otentikasi pada Citra Manipulasi Menggunakan Metode Least Significant Bit - Ardhi Fadlika Satria; Riza Ibnu Adam; Carudin Carudin (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
The use of digital platforms has both positive and negative effects. Many criminals who manipulate images for personal gain, so as to harm the copyright holder (ownership) of the image. The purpose of the study was to detect false imagery generated by copy-move, splicing, and retouching techniques. The method used is the Least Significant Bit (LSB) method as a watermarking technique and its detection features. The insertion process is carried out on watermark images into the cover image as the container media. Image owners can authenticate to prove the originality of the image when the extraction process is done, the image manipulation is successfully detected because it is damaged. The test results showed that the digital watermarking technique with the Least Significant-Bit method is able to protect and prove the authenticity of the image. It was concluded that the results of comparison of watermark extraction on the original image and manipulation image saw a very significant difference in terms of visual and calculation with MSE, RMSE, and PSNR parameters.